Peanut Pods (Arachis hypogaea L.) In Ex-Mining Limestone Soil Enriched with Indigenous Bacteria - Riska Andriani; Hesti Kurniahu; Sriwulan Sriwulan; Annisa Rahmawati (Biota, 2021)
Pioneer plants are found in the former limestone mining area, and there are bacteria in their root systems. These bacteria can be used as biofertilizers. This study aims to find out the use of indigenous PGPR in ex-mining limestone land to be able to increase the yield of pea (Arachis hypogaea L.) var. Tuban. This research was an experimental study with 5 treatments applying indigenous PGPR at concentrations of 0%, 25%, 50%, 75%, and 100% and consist of 5 replications. Stages of research include planting peanuts (Arachis hypogaea L.) var. Tuban by adding indigenous PGPR with the same dose and source in an environment with sufficient sunlight. The parameters observed were biomass, pithy weight, empty pod weight, wet weight, dry weight, pH, and temperature of the planting medium for peanuts. In this study, the results showed that the concentration of PGPR 25% had a significant effect on the dry weight of peanuts and doesn’t had significant effect on biomass. Meanwhile, the provision of PGPR with different concentrations did not have a significant effect on the temperature and pH of the lime mining soil planting media